APOPTOTIC ACTIVITY AS A TRIGGER MECHANISM OF SYSTEMIC FIBROSIS OF INTERNAL ORGANS IN MINERS - Бондарев, Олег Иванович; Мальцева, Нина Васильевна; Сурков, Арнольд Михайлович; Бондарева, Ирина Анатольевна; Азаров, Павел Алексеевич (Medicine in Kuzbass, 2022)
The subject of the study (observations). Questions of the apoptotic process in the development of fibroplastic changes in pneumoconiosis in miners.The purpose of the study – to substantiate the contribution of the genetic factor associated with genome polymorphism in the development of dust pathology in miners. Identification of gene variants as markers of individual predisposition to the development of pneumoconiosis.Research methods. Theoretical basis.
Keywords: fibroplastic changes; dust pathology; pneumoconiosis; gene polymorphism; apoptosis